High-speed synchrotron X-ray imaging of melt pool dynamics during ultrasonic melt processing of Al6061 - Lovejoy Mutswatiwa; Lauren Katch; Nathan J Kizer; Judith A Todd; Tao Sun; Samuel J Clark; Kamel Fezzaa; Jordan S Lum; David M Stobbe; Griffin Jones; Kenneth C Meinert; Andrea P Argüelles; et al. (Communications Materials, 2024)
Abstract Ultrasonic processing of solidifying metals in additive manufacturing can provide grain refinement and advantageous mechanical properties. However, the specific physical mechanisms of microstructural refinement relevant to laser-based additive manufacturing have not been directly observed because of sub-millimeter length scales and rapid solidification rates associated with melt pools. Here, high-speed synchrotron X-ray imaging is used to observe the effect of ultrasonic vibration directly on melt pool dynamics and solidification of Al6061 alloy. The high temporal and spatial resolution enabled direct observation of cavitation effects driven by a 20.2 kHz ultrasonic source. We utilized multiphysics simulations to validate the postulated connection between ultrasonic treatment and solidification. The X-ray results show a decrease in melt pool and keyhole depth fluctuations during melting and promotion of pore migration toward the melt pool surface with applied sonication. Additionally, the simulation results reveal increased localized melt pool flow velocity, cooling rates, and thermal gradients with applied sonication. This work shows how ultrasonic treatment can impact melt pools and its potential for improving part quality.